Caracterização familiar e intervenção em grupo com irmãos de indivíduos com transtorno do espectro do autismo - Goto, Paula Hisa Paranaíba (2017)
Siblings of people with ASD could develop social and emotional problems, also, they could have difficulties in parental relationship. Group intervention could be a way to support those siblings with typical development on clarifying their doubts, sharing experiences, and learning strategies to deal with their ASD siblings’ daily relationship. The goal of this study is to present a report of a group intervention with ASD siblings and its effects upon these variables: behavior issues and social behavior; stress and confrontation strategies; relationship network and knowledge about ASD, in addition, the parents and caregivers’ satisfaction related to the intervention. The design used was a quasi-experimental design with three groups: experimental group (EG) which received the whole intervention, partial group (PG) which received a partial intervention, and control group (CG) which did not receive the intervention. There were pre-and post-test to all of the groups but a six months follow-up only with EG. The EG participants were six siblings with age ranging from10 to 15 years old, PG participants were four siblings with age ranging from10 to 12 years old, and the CG participants were four siblings with age ranging from 8 to 12 years old. All the groups had participants with both genders. There were five meetings with EG (12 hours total) and three meetings with PG (6 hours total). Emotional aspects and information were developed in these meetings. In total, 15 siblings and their parents and caregivers participated of the research. One child participated only of the pre-test stage. The protocols used were Strengths and Difficulties Questionnaire (SDQ), Stress and Coping in Siblings, Network of Relationships Inventory (NRI), Childhood Autism Rating Scale (CARS), satisfaction questionnaire with every meeting activities, and a parent /caregiver questionnaire, two semi structured interview scripts, one was used with the research participants, and the other with parents and caregivers. The results showed positive changes related to ASD knowledge, confrontation strategies optimization and for the two intervention groups, a pro-social behavior improvement. There were not changes related to difficulties, stress and relationship networks. The participants reported they enjoyed the activities, so did their parents and caregivers related to the intervention. For future studies, it would be important to consider a large intervention time and the number of participants. Also, a statistical analysis should be considered for future studies to check if the changes were significant to correlate them to gender, birth order, ASD level and the results of the protocols used. Parallel Interventions with ASD parents and siblings could be an interesting possibility. Besides the research limitations, this is a pioneer study in this country. It has showed the importance of a place where the ASD siblings could be heard, received information and support, because they could be benefited from professionals’ attention. Group intervention is beneficial when considering experience changes and time and resources optimization. But also, there are specific cases, especially when high stress levels and disruptive behaviors are presented, that individualized attention could be essential.